Brincar na Rua. Desenhar (n)o espaço público - Joana Fonseca Maia (2012)
'Play on the Street' is to look for the intimacy 'between' inner and outer space. 'Play on the Street' is to disturb geometric certainties,exaggerate the perception of image and face up to danger. 'Play on the Street' is the wanted city, mixture of knowledge, mystery,encounters, !eedom, transgression, privacy and profoundness of collective life.'Play on the Street' manifests itself through the timeless anonymous architect. "e concave street comes !om the attentive innerobservance to the scale of detail. "e street is the stage adapted to human action. In it public spaces suitable for walking andstopping brought by the inhabited word which supports security and citizenship converge. "e need put before daily life takes thestreet requesting orientation and identi#cation !om it. "e design of the street, both geometric and organic, requires the presenceof materialised refuges within its limits (between inner and outer) revealing smoothness and solidarity when in permanent connection:play ground.[Presentation: "e Street is Obvious.]'Play on the Street' emerges consistently on the architectural design !om the 20th century. Ludus, limen e paídía shape a spiralwhich characterises a transformation process recognising the values of formation, deformation and questioning."e design rationalised by modernism divides and categorises space. "e duly equipped 'emptiness', #t to the e$ciency of eachhuman function, reveals the shape of a city / society that is segregated by that which has been a linear urban thought. 'Play on theStreet' meets its focus inside its buildings.Time for suspension reserved for criticism and the return to the essential causes is surpassed by the voice of the 'child' who onceretracted into its hiding place has always known how to consciously #nd its belonging place - the street with which it is so intimate."e public place is conceptually resumed as a vernacular entity, the 'between' private and public as this de#nes the new quality oflife and the quality of citizenship of its inhabitants. Urbanism is reborn !om the social life generated by the heterogeneous welcomingof multi-functioning encounters on the street. "e design intuited by the desire of each individual entity is read and functions in various manners, the social whole is entirelycomplex and contradictory. To explore uncertainties putting solidity, scale and beauty at risk holds on the space of the street the!eedom of the transgression of playing. "e design of the public space is thus a political manifest of collective ideas. Involved inchaos, conventional order is recognised so it can be broken or modi#ed in a way as to include valid exceptions - the authenticationof ambiguity. "e street communicates - sign and system - and demands its constant readjustment and identi#cation.[Development:'Play on the Street' is the cause for the architectural preposition']